The Art of Social Theory - Swedberg, Richard (Book collections on Project MUSE., 2014)
In the social sciences today, students are taught theory by reading and analyzing the works of Karl Marx, Max Weber, and other foundational figures of the discipline. What they rarely learn, however, is how to actually theorize. The Art of Social Theory is a practical guide to doing just that. In this one-of-a-kind user's manual for social theorists, Richard Swedberg explains how theorizing occurs in what he calls the context of discovery, a process in which the researcher gathers preliminary data and thinks creatively about it using tools such as metaphor, analogy, and typology.